Chains - Anderson, Laurie Halse (New York Scholastic, 2008)
When their owner dies at the start of the Revolution, Isabel and her younger sister are sold to Loyalists in New York, where Isabel is offered the chance to spy for the Patriots.
Sequel: Forge.
Ages 10 up.
Keywords: Slavery -- Fiction; African Americans -- Fiction; Spies -- Fiction; New York (N.Y.) -- History -- Revolution, 1775-1783 -- Juvenile fiction; New York (N.Y.) -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction